Aglomeration Analysis Of The Processing Industry On Economic Growth In Bangka Barat District - Ayu Wulandari; Hidayati Hidayati (Integrated Journal of Business and Economics (IJBE), 2021)
The development of the manufacturing sector in the Province of the Bangka Belitung Islands is a long-term development. This is because the contribution of the manufacturing industry sector is very large to the formation of GRDP in the Province of the Bangka Belitung Islands. One of the regencies in the Bangka Belitung Islands Province that has the highest contribution from the manufacturing sector to GRDP is West Bangka Regency. The large contribution of the manufacturing sector in West Bangka Regency will encourage grouping due to the encouragement of various factors called economic agglomeration. This study analyzes the agglomeration of the processing industry in West Bangka Regency on economic growth. With the documentation technique, namely by obtaining secondary data and information from written reports and published data and to increase the sharpness of the analysis, interviews (in-dept interviews) were also conducted to informants who were considered to have extensive information on the research conducted. In addition, quantitative data analysis through simple regression is also used to see the relationship between the agglomeration variables of the manufacturing industry and its economic growth. The results showed that the level of industrial agglomeration in West Bangka Regency was still low. The new industrial agglomeration was formed in 2020 because the index value was 2.9614 or categorized as medium agglomeration. Then the results of the t-count show that there is no significant influence between Industrial Agglomeration on economic growth in West Bangka Regency